1992
DOI: 10.1212/wnl.42.3.473
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for the diagnosis of ischemic vascular dementia proposed by the State of California Alzheimer's Disease Diagnostic and Treatment Centers

Abstract: Accurate diagnosis of vascular dementia is important for the recognition of underlying pathophysiology and the institution of appropriate therapy. It is also important for the determination of the incidence and prevalence of not only vascular dementia but also Alzheimer's disease (AD), since differentiating between these two entities is often problematic. The State of California Alzheimer's Disease Diagnostic and Treatment Centers (ADDTC) herein propose criteria for the diagnosis of ischemic vascular dementia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
659
1
17

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,119 publications
(683 citation statements)
references
References 0 publications
6
659
1
17
Order By: Relevance
“…The presence of progressive disease associated with white-matter changes was referred to as 'probable vascular dementia'. 21,22 Currently, there is general agreement about the diagnosis of VCI in patients with large vessel strokes due to either thrombosis or embolism, which can be readily seen on neuroimaging. 2 Some of these multi-infarct patients show a cognitive decline with each stroke.…”
Section: Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The presence of progressive disease associated with white-matter changes was referred to as 'probable vascular dementia'. 21,22 Currently, there is general agreement about the diagnosis of VCI in patients with large vessel strokes due to either thrombosis or embolism, which can be readily seen on neuroimaging. 2 Some of these multi-infarct patients show a cognitive decline with each stroke.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Initial attempts to standardize diagnostic criteria for multi-infarct dementia required the temporal relationship of the stroke to the decline in cognition, which failed to occur in many patients with a progressive course, which more closely resembled neurodegeneration. 21,22 Although temporal relationship between the infarct and the loss of cognitive function was considered as critical for diagnosis, it was soon realized that many patients with vascular causes of dementia had a progressive course that overlapped in the early stages with AD, while MRI showed that many of these patients had abnormal signal in the white matter, suggesting possible cerebrovascular disease.…”
Section: Definitions Of Vascular Cognitive Impairmentmentioning
confidence: 99%
“…The diagnosis of SVaD was on the basis of Erkinjuntti's brain imaging criteria (Erkinjuntti et al, 2000) and ADDTC (Alzheimer's Disease Diagnostic and Treatment Centers) criteria (H. C. Chui et al, 1992) for probable or possible VaD. The diagnosis of svMCI was on the basis of Erkinjuntti's brain imaging criteria (Erkinjuntti et al, 2000), Peterson's criteria (Petersen, 2004) with the following modifications which were previously described (Noh et al, 2014) cerebral GM volume reduction, cognitive deficits, SVaD, svMCI (SDMT), and Verbal Fluency Test (VFT).…”
Section: Subjectsmentioning
confidence: 99%
“…The clinical evaluation included examination and diagnostic consensus by a neurologist, neuropsychologist, psychiatrist, and a social worker. Inclusion criteria for all earlier studies included evidence of a mild to moderate dementia (Mini-Mental State Examination; MMSE Ő†10 and Ő…26) and diagnosis of probable AD (McKhann et al, 1984), probable0possible ischemic vascular dementia (Chui et al, 1992) (VaD), or both (mixed AD0VaD). For this study, all participants were analyzed as a single group.…”
Section: Participantsmentioning
confidence: 99%